Systematic Literature Review: How Can Effective Laboratory Planning Improve the Quality of Science Education? - Hakim, M. Arif Rahman; Hamidah, Afreni (Department of Physics Education, Universitas Mataram, 2025)
This study aims to systematically evaluate how effective laboratory planning can improve the quality of Science Education (IPA) learning. A Systematic Literature Review (SLR) was conducted by analyzing 20 articles published over the last seven years, focusing on laboratory management, planning, and its impact on the learning process. The research found that well-planned laboratories, supported by adequate facilities, competent staff, and integration with the curriculum (including the Merdeka curriculum), provide more meaningful learning experiences for students. Additionally, innovations such as interactive digital media and Project-Based Learning (PjBL) models enhance the effectiveness of practical activities. The study also highlights the role of laboratories in fostering social values and character development, aligning with the Pancasila Learner Profile. Moreover, virtual laboratories were identified as an effective alternative in areas with limited infrastructure. The findings suggest that comprehensive and adaptive laboratory planning is crucial for improving IPA learning quality. The study recommends that schools and educational policymakers prioritize laboratory management aspects, such as enhancing laboratory staff capacity, acquiring modern practical media, and providing teacher training in managing laboratories based on curriculum innovation. Effective laboratory planning is expected to contribute to the achievement of holistic and sustainable IPA learning goals.